Postinflammatory hyperpigmentation after human cold pain testing. (August 2016) - Wolz, Melissa J.; Sadler, Katelyn E.; Long, Caela C.; Brenner, Daniel S.; Kim, Brian S.; Gereau, Robert W.; Kolber, Benedict J.
Abstract : Abstract: Changes in cold temperature sensitivity are often associated with chronic pain conditions. Progress in understanding the neurobiological mechanism underlying these changes and resulting development of effective therapies has been slowed by the accessibility and affordability of devices used to measure thermal sensitivity in humans. To address this gap, we developed an inexpensive method to measure cold pain thresholds in healthy adult volunteers using dry ice and a thermode. However, early in preliminary testing, a subject presented with epidermal postinflammatory hyperpigmentation that lasted for >200 days. Although this response was unique among the small number of subjects in development of the assay, it raised questions as to the safety of the assay design. Abstract : After assessment of thermal sensitivity during development of a novel cold pain assay, one subject developed postinflammatory hyperpigmentation. Resultant epidermal darkening gradually faded without clinical intervention.